Testosterone Deficiency: A Review and Comparison of Current Guidelines. Issue 6 (9th May 2019) - Kwong, Jethro C.C.; Krakowsky, Yonah; Grober, Ethan
ABSTRACT: Background: There is much controversy regarding the appropriate evaluation and management of testosterone deficiency (TD). Aim: To compare current guidelines on the evaluation and management of TD to provide clarity for patients and clinicians, as well as to highlight areas of controversy. Methods: A literature search of MEDLINE, Embase, Cochrane Library, and various association websites was performed to identify guidelines for TD. Outcomes: Key aspects in the approach were compared, with a focus on the biochemical definition (cutoff) for low testosterone (T), principles of management, and recommendations for testosterone therapy (TTh) in special patient populations. Results: Guidelines from the Canadian Medical Association Journal, American Urological Association, European Association of Urology, Endocrine Society, International Society for Sexual Medicine, and British Society for Sexual Medicine were included for review. Recommendations were generally consistent across guidelines. Key differences include the biochemical cutoff for low T, and recommendations for patients with low to normal T, prostate cancer, or cardiovascular disease. We highlight several case scenarios in which management differs depending on the guideline adopted. Clinical Implications: Although general diagnostic and management principles are in agreement across the guidelines, notable differences may impact patient diagnosis and eligibility for TTh. Strengths & Limitations: Only guidelines written in English were included. The quality of the included guidelines was not evaluated, but this was beyond the scope of this review. Conclusion: We highlight the limitations of relying exclusively on guidelines in managing patients with TD.